The effect of term limits on legislative productivity senators in the 13th to 16th Congress of the Philippines - Romero, Regina Yvette V. (School of Economics, University of the Philippines Diliman, 2019)
The legislators from the House of Representatives under the Seventeenth Congress of the Philippines proposed a bill on the abolishment of term limits in the Congress. This paper aims to examine whether senators of the 13th to 16th Congress are more productive in terms of two indicators_ 1) being principal authors, and 2) being principal authors and sponsors, if they are facing term limits. Further, this aims to discern the possible policy implications based on the results. The researcher constructed a panel dataset, and used Linear and Poisson Regression models under fixed and random effects cases to determine the relationship between senators who are facing term limits and their legislative productivity. Results show that controlling for other explanatory variables, senators who are facing term limits are more productive in terms of introducing and sponsoring bills using the Poisson Regression model.